2011
DOI: 10.1159/000330237
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Nutritional Genomics Teaching in Undergraduate Dietetic Curricula

Abstract: Nutritional genomics offers great promise to personal health management based on the understanding of the relationship between diet, gene expression and health outcomes. Our readiness to deliver nutrigenetic-based nutrition education has been slow due to the complexity of gene-nutrient interaction and interplays between many disciplines such as genetics, nutrition, biostatistics, sociology, law and philosophy in the process. To make a public impact, we must prepare future allied health professionals with knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…A good example is the study of Fang et al [25], who showed that providing additional nutrigenomics courses to dietetics students resulted in an increased interest in nutrigenomics and improvements in students’ knowledge. A potential solution has also been presented by Prasad et al [26], who proposed a detailed plan for improving nutrigenetic and nutrigenomic education in dietetic curricula. However, the implementation of this program may be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…A good example is the study of Fang et al [25], who showed that providing additional nutrigenomics courses to dietetics students resulted in an increased interest in nutrigenomics and improvements in students’ knowledge. A potential solution has also been presented by Prasad et al [26], who proposed a detailed plan for improving nutrigenetic and nutrigenomic education in dietetic curricula. However, the implementation of this program may be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of genetic variants that may predispose individuals to chronic disease is not well established and may therefore pose a significant barrier to nutrigenomics-based personalized nutrition [62]. For clinical application of genetic knowledge, a health professional needs to know how to interpret genetic and molecular tests and to extract the necessary information for planning dietary interventions [76]. Because of this, genetic nutritional education is needed for health professionals at the forefront of advances in nutrigenomics [74].…”
Section: Ethical Legal and Social Aspects In Nutrigeneticsmentioning
confidence: 99%
“…Because of this, genetic nutritional education is needed for health professionals at the forefront of advances in nutrigenomics [74]. Further, it is urgent that courses in nutritional genetics are included in the university curriculum [75,76] in order to educate and orientate a new generation of professionals, the nutrigenomicists [74]. …”
Section: Ethical Legal and Social Aspects In Nutrigeneticsmentioning
confidence: 99%
“…2 Nutrigenetics and nutrigenomics training are not traditional components of nutrition and dietetics course curricula; only over the last few years has this science been included in some courses. 3 For dietitians and nutritionists trained prior to the development of this area of science (and subsequent inclusion in some dietetic and nutrition courses), the complexity of the topic may be confusing and unclear, and access to appropriate training and information may be difficult. 4 International surveys 5,6 indicated that dietitians in Australia, US and UK have low knowledge and confidence in applying nutritional genomics in their practice.…”
Section: Introductionmentioning
confidence: 99%